“Having to Shift Everything We’ve Learned to the Side”: Expanding Research Methods Taught in Psychology to Incorporate Qualitative Methods - Roberts, Lynne D.; Castell, Emily (Frontiers in Psychology, 2016)
In Australia the tradition of conducting quantitative psychological research within a positivist framework has been challenged, with calls made for the inclusion of the full range of qualitative and quantitative methodologies within the undergraduate psychology curriculum. Despite this, the undergraduate psychology curriculum in most Australian universities retains a strong focus on teaching quantitative research methods. Limited research has examined attitudes toward qualitative research held by undergraduate psychology students taught within a positivist framework, and whether these attitudes are malleable and can be changed through teaching qualitative methodologies. Previous research has suggested that students from strong quantitative backgrounds experience some cognitive dissonance and greater difficulties in learning qualitative methods. In this article we examine third year undergraduate psychology students’ attitudes to qualitative research prior to commencing and upon completion of a qualitative research unit. All students had previously completed two 13 week units of study in quantitative research methods. At Time 1, 63 students (84.1% female) completed online surveys comprising attitudinal measures. Key themes to emerge from student comments were that qualitative research was seen as an alternative approach, representing a paradigmatic shift that was construed by some students advantageous for meeting future professional and educative goals. Quantitative measures of attitudes to qualitative research were associated with general attitudes towards research, and psychology-specific epistemological beliefs. Changes in attitudes following completion of the qualitative research methods unit were in the hypothesized direction, but non-significant (small effect sizes). The findings increase our understanding of psychology students’ attitudes towards qualitative research and inform our recommendations for teaching research methods within the undergraduate psychology curriculum.